CLINICAL FINDINGS AND MANAGEMENT OF ANGLE RECESSION GLAUCOMA: A CASE REPORT - Madona Debora; Maulida Rifada; Andika Prahasta; Elsa Gustianty (Majalah Oftalmologi Indonesia, 2022)
Introduction: Angle recession is a common finding after blunt trauma and involves a tear between the longitudinal and circular fibers of ciliary body. The incidence of angle recession was 24.3%. It may occur months to years after ocular trauma. Purpose: To report clinical findings and management of a patient with angle recession glaucoma. Case report: A 51 years old female came with chief complaint of blurry vision of left eye since five months earlier. There was a history of trauma in left eye 26 years ago. She had been treated with antiglaucoma medication by an ophthalmologist. Visual acuity of right eye was 1.0 and left eye was light perception. Applanation Tonometer Goldmann of left eye was 42 mmHg. Slit lamp examination revealed traumatic iritis and lens opacity. Gonioscopy revealed widening of ciliary body band in three quadrants. Funduscopy showed cup/disc ratio enlargement and RNFL thinning. This patient was diagnosed as angle recession glaucoma with traumatic iritis and traumatic cataract. Combined phacoemulsification-trabeculectomy with intraocular lens implantation was performed. One month after surgery, intraocular pressure decreased with improvement of visual acuity. Conclusion: Classically clinical findings of angle recession glaucoma were unilateral glaucoma with history of trauma and widening of ciliary body band. Surgery is needed in uncontrolled intraocular pressure with medication. Combined phacoemulsification-trabeculectomy decreases intraocular pressure as well as improves visual acuity.